Real-time system for studies of the effects of acoustic feedback on animal vocalizations - Skocik, Mike; Kozhevnikov, Alexay (Frontiers in Neural Circuits, 2013)
Studies of behavioral and neural responses to distorted auditory feedback can help shed light on the neural mechanisms of animal vocalizations. We describe an apparatus for generating real-time acoustic feedback. The system can very rapidly detect acoustic features in a song and output acoustic signals if the detected features match the desired acoustic template. The system uses spectrogram-based detection of acoustic elements. It is low-cost and can be programmed for a variety of behavioral experiments requiring acoustic feedback or neural stimulation. We use the system to study the effects of acoustic feedback on birds' vocalizations and demonstrate that such an acoustic feedback can cause both immediate and long-term changes to birds’ songs.